Predictive Factors Associated with Pain Relief of Spinal Cord Stimulation for Central Post-stroke Pain - TANEI, Takafumi (Neurol Med Chir (Tokyo), 2019)
The efficacy and predictive factors associated with successful spinal cord stimulation (SCS) for central post-stroke pain (CPSP) have yet to be definitively established. Thus, this study evaluated the rates of pain relief found after more than 12 months and the predictive factors associated with the success of SCS for CPSP. The degree of pain after SCS in 18 patients with CPSP was assessed using the Visual Analog Scale preoperatively, at 1, 6 and 12 months after surgery, and at the time of the last follow-up. After calculating the percentage of pain relief (PPR), patients were separated into two groups. The first group exhibited continuing PPR ≥30% at more than 12 months (effect group) while the second group exhibited successful/unsuccessful trials followed by decreasing PPR <30% within 12 months (no effect group). Pain relief for more than 12 months was achieved in eight out of 18 (44.4%) patients during the 67.3 ± 35.5 month follow-up period. Statistically significant differences were found for both the age and stroke location during comparisons of the preoperative characteristics between the two groups. There was a significantly younger mean age for the effect versus the no effect group. Patients with stoke in non-thalamus were significantly enriched in effect group compared with those with stoke in thalamus. Multivariable analysis using these two factors found no statistical differences, suggesting that these two factors might possibly exhibit the same behaviors for the SCS effect. These results suggest that SCS may be able to provide pain relief in young, non-thalamus stroke patients with CPSP.